Achilles Tendinopathy: Epidemiology, Diagnosis, and Treatment Strategies – A Review - Dziekoński, Kamil; Popiel, Michal; Wieczorek, Iga; Cybulski, Paweł; Gorycki, Hubert; Wacławek, Wiktoria; Matwiejuk, Weronika; Samek, Julia; Komorowski-Roszkiewicz, Jakub; Marcyś, Karol; Redner, Aneta; Usowska, Karolina (Quality in Sport, 2025)
This review presents a comprehensive synthesis of current knowledge on Achilles tendinopathy (AT), focusing on its epidemiology, diagnostic approaches, and available treatment strategies. AT is a common musculoskeletal disorder, particularly among athletes, with a multifactorial etiology and a clinical presentation that includes localized pain and functional impairment. While diagnosis is primarily clinical, imaging modalities such as ultrasound and MRI play an essential role in supporting clinical judgment and differentiating among tendon pathologies. The review identifies eccentric exercise as the most effective conservative treatment, often used in combination with extracorporeal shock wave therapy and pharmacological agents to enhance outcomes. Surgical intervention is considered in chronic or refractory cases and has shown favorable results in selected patients. Despite progress in understanding and managing AT, challenges remain in the form of inconsistent diagnostic criteria, variability in therapeutic outcomes, and limited high-quality evidence supporting newer pharmacological interventions. Emerging techniques in diagnostic imaging and rehabilitation continue to evolve, offering promising avenues for improving clinical outcomes. This review highlights the importance of individualized treatment approaches and identifies key areas for future research, such as the standardization of diagnostic measures, optimization of rehabilitation protocols, and evaluation of novel therapies. By consolidating the latest evidence, this article provides valuable insights for clinicians, researchers, and sports medicine professionals seeking effective, evidence-based strategies to manage and treat Achilles tendinopathy.